I have the sequence: 1, 16, 166, 1666 . Im trying to find the nth term for this sequence but since it is not linear or geometric I'm not sure how to. I worked out that the recursive formula is: \begin{gather} a_1 = 1 \\ a_{n + 1} = 10a_{n} + 6 \end{gather} I'm trying to write this as an nth term and I saw that one solution was: \begin{gather} \frac{1}{6}\left ( 10 ^{n}-4\right ) \end{gather} But I don't know how to derive this. I have seen other answers on this site but the explanations arent often very clear or involve math that is beyond my ability. For reference I am a high schooler in my final year, if anyone is familiar with the British Education system I am studying further maths for a level so I don't know any math more complex than that. Thank you

  • $\begingroup$ Why need a formula. It's clearly $1\underbrace{666...6}_{n-1}$. Why do you mean algebraic formula. But... I'll post and answer. $\endgroup$
    – fleablood
    Feb 14, 2021 at 9:42
  • $\begingroup$ Hint: show that $(u_n+2/3)_n$ is geometric. $\endgroup$
    – Aphelli
    Feb 14, 2021 at 9:49

3 Answers 3


$a_n = 1\underbrace{6666...6}_{n-1}=$

$1\underbrace{0000.....0}_{n-1} + \underbrace{666...6}_{n-1} =$

$10^{n-1} + 6\cdot \underbrace{111....1}_{n-1} =$

$10^{n-1} + 6\cdot \frac {\underbrace{9999....9}_{n-1}}9 =$

$10^{n-1} + 6\cdot \frac {10^{n-1} -1}9=$

$10^{n-1} + \frac 23(10^{n-1} -1) =$

$\frac {3\cdot 10^{n-1} +2\cdot 10^{n-1} - 2}3=$

$\frac {5\cdot 10^{n-1} -2}3$.



$a_n = 1\underbrace{6666...6}_{n-1}$

$3a_n = 4\underbrace{99999...9}_{n-2}8=$

$5\underbrace{00000.....0}_{n-1} - 2$

$5\cdot 10^{n-1} -2$

So $a_n = \frac {5\cdot 10^{n-1} -2}3$


Observe that $1/6= 0.1666\dots $ and $a_n = 10^n(0.1666\dots - \varepsilon_n)$, where $\varepsilon_n = 10^{-n}\cdot 0.666 \dots$. Since $\varepsilon_n$ is geometric for every $n$, you can have a closed expression which is $$\varepsilon_n = 10^{-n} \cdot \dfrac{4}6. $$ Hence, $$a_n = \dfrac{1}{6} \bigg(10^n - 4\bigg).$$


The Online Encyclopedia of Integer Sequences A246057 shows$\quad a(n) = (5\times10^n - 2)/3$

It generates $\\ 16\quad 166\quad 1666\quad 16666\quad 166666\quad 1666666\quad 16666666\quad 166666666\quad \cdots$

Working backwards, we see that all of these number resemble $x+\dfrac23$ so we can try $$3\times 16=48\qquad 3\times 166=498\qquad 3\times1666=4998 \quad\cdots\quad $$

and we can see that each is $2$ short of $5\times10^n.\quad$ From here it should be easy to see how the formula was developed and how it works.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.